The Influence of Firm Value, Financial Performance, and Good Corporate Governance on the Quality of Sustainability Reporting - Novaldi, Mastrio; Muhyarsyah, Muhyarsyah (Sekolah Tinggi Manajemen IPMI, 2025)
The growing importance of sustainability in business operations has encouraged companies to increasingly pay attention to and report on their social, environmental, and economic performance. Modern companies are expected to consider broader interests beyond just management and shareholders. Investors no longer rely solely on balance sheets, income statements, cash flows, and notes to financial statements when making investment decisions. There is a growing demand from stakeholders for company reports that contain more holistic information about the company's long-term value creation opportunities and its broader impact on society. Although many companies have published Sustainability Reports or ESG Reports, these reports are often fragmented and inconsistent, making stakeholder decision making more challenging (Global Head of IFRS & ESG Reporting, PwC United Kingdom). This study aims to examine the influence of firm value, solvency ratio, profitability ratio, leverage ratio, shareholders, and board of commissioners on the quality of sustainability reporting. A causal research method is applied in this study. A total population of 60 companies is used in the study, with 30 companies selected using purposive sampling based on specific criteria. The study's findings indicate that firm value, solvency ratio, profitability ratio, managerial ownership, and institutional ownership have a positive and significant influence on sustainability reporting, as evidenced by the t-test results showing t values greater > t values table.